Valuation of forward start options under affine jump-diffusion models. Issue 5 (3rd May 2016) - Nunes, João Pedro Vidal; Alcaria, Tiago Ramalho Viegas
Abstract : Under the general affine jump-diffusion framework of Duffie et al. [ Econometrica, 2000, 68, 1343–1376], this paper proposes an alternative pricing methodology for European-style forward start options that does not require any parallel optimization routine to ensure square integrability. Therefore, the proposed methodology is shown to possess a better accuracy–efficiency trade-off than the usual and more general approach initiated by Hong [Forward Smile and Derivative Pricing. Working paper, UBS, 2004] that is based on the knowledge of the forward characteristic function . Explicit pricing solutions are also offered under the nested jump-diffusion setting proposed by Bakshi et al. [ J. Finance, 1997, 52, 2003–2049], which accommodates stochastic volatility and stochastic interest rates, and different integration schemes are numerically tested.